X-Linked Adrenal Hypoplasia Congenita in a Boy due to a Novel Deletion of the Entire NR0B1 (DAX1) and MAGEB1–4 Genes - Aleksandra Rojek; Maciej R. Krawczynski; Aleksander Jamsheer; Anna Sowinska-Seidler; Barbara Iwaniszewska; Ewa Malunowicz; Marek Niedziela (International Journal of Endocrinology)
X-linked Adrenal Hypoplasia Congenita (AHC) is caused by deletions or point mutations in the NR0B1 (DAX1) gene. We present a boy with AHC who came at the age of 25 days in a severe state due to prolonged vomiting and progressive dehydration. Laboratory studies showed prominent hyponatremia and hyperkaliemia but not hypoglycemia. Primary adrenal insufficiency was confirmed with low serum cortisol levels and high plasma ACTH levels. Hydrocortisone therapy combined with saline and glucose infusions was started immediately after blood collection. Two exons of the NR0B1 (DAX1) gene were impossible to amplify using the standard PCR method. Array CGH was used to confirm the putative copy-number variation of NR0B1 (DAX1) revealing a novel hemizygous deletion encompassing the entire NR0B1 (DAX1) gene together with the MAGEB genes. This genetic defect was also present in heterozygosity in the patient’s mother. We show that NR0B1 (DAX1) gene analysis is important for confirmation of AHC diagnosis and highlights the role of genetic counseling in families with AHC patients, particularly those with X chromosome microdeletions, covering more than NR0B1 (DAX1) alone. We hope that further clinical follow-up of this patient and his family will shed a new light on the role of MAGEB genes.